A Comprehensive Review on Potential Molecular Drug Targets for the Management of Alzheimer's Disease - Sharma, Chanchal; Mazumder, Avijit (Central Nervous System Agents in Medicinal Chemistry, 2024)
Alzheimer's disease (AD) is an onset and incurable neurodegenerative disorder that has been linked to various genetic, environmental, and lifestyle factors. Recent research has revealed several potential targets for drug development, such as the prevention of Aβ production and removal, prevention of tau hyperphosphorylation, and keeping neurons alive. Drugs that target numerous ADrelated variables have been developed, and early results are encouraging. This review provides a concise map of the different receptor signaling pathways associated with Alzheimer's Disease, as well as insight into drug design based on these pathways. It discusses the molecular mechanisms of AD pathogenesis, such as oxidative stress, aging, Aβ turnover, thiol groups, and mitochondrial activities, and their role in the disease. It also reviews the potential drug targets, in vivo active agents, and docking studies done in AD and provides prospects for future drug development. This review intends to provide more clarity on the molecular processes that occur in Alzheimer's patient's brains, which can be of use in diagnosing and preventing the condition.
Keywords: Alzheimer' s disease